(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
Undergraduate Law Students training is organized in such a way that they can multi-task through diverse activities ranging from classroom discussions, understanding the principles of law and mastering legal arguments, participating in mock and moot trial, clinical legal education and studying. These activities make them become better lawyers after graduation however they have also become challenges documented to lead to psychological trauma for some students. Extensive literature review, content analysis as well as interview methods were used. The conceptual framework of the study was based on analysis of 3 Autobiographies and literature review. Autobiographies by Bisi Adeleye-Fayemi and Chimamanda Ngozi Adichie were selected. They are: “Where is your Wrapper”, “Speaking above a whisper” and “We should all be Feminist”. Texts from these autobiographies that answered the research questions were selected for annotations; they providence research evidence showing that autobiographies can be used as bibliotherapy intervention in handling psychological trauma that could arouse from activities in law faculty environment. A structured interview carried out on a medical doctor (director) in a government hospital, when placed in juxtaposition with results of literature review, showed that law environment is not the only stressor to undergraduate law students. Background factors to each student were also found to contribute to psychological trauma in law environment. Hence it was concluded that bibliotherapy was essential intervention technique for undergraduate law students. It was further shown that academic law libraries can be a medium of bibliotherapy intervention for law undergraduates.